Analysis of financial ratio to profit growth at PT. Bank Mestika Dharma TBK Medan listed on the Indonesian Stock Exchange / Nadana Syafrina Siregar and M. Nelson Pinem - Siregar, Nadana Syafrina; Pinem, M. Nelson (Center for Islamic Philantrophy & Social Finance (CIPSF), 2024)
The reason for this examination is to find out and break down the monetary proportions to benefit development at PT. Bank Mestika Dharma Tbk Medan, which is recorded on the Indonesia Stock Exchange. This examination is restricted to PT. Bank Mestika Dharma Tbk Medan, which is recorded on the Indonesia Stock Exchange. This sort of exploration is unmistakably quantitative, with the object of examination being the monetary side of PT. Bank Mestika Dharma Tbk. The information source utilized is optional information, in particular the organization's monetary report information as an accounting report and pay proclamation. In light of the consequences of testing and examination of liquidity, dissolvability and benefit of PT. Bank Mestika Dharma Tbk Medan in 2020–2022, the organization is sorted as bad. This is on the grounds that the investigation of liquidity and dissolvability of PT. Bank Mestika Dharma Tbk Medan is illiquid on the grounds that paying debts is less capable. In the meantime, in the benefit examination, it changed in light of the fact that it was still under the business normal norm.